Electrical characterization of two-dimensional materials and their heterostructures - Arora, H.; Seifert, G.; Cuniberti, Gianaurelio (Giovanni); Helm, M.; Erbe, A. (2016 IEEE Radio and Antenna Days of the Indian Ocean, RADIO 2016, 2016)
Two-dimensional (2D) materials have gained enormous attention in recent years owing to their excellent transport properties and mechanical flexibility. Several 2D materials like graphene, MoS2, h-BN are under intense study in the areas of electronics, optics and sensing. Apart from these materials, 2D polymers are also rapidly gaining attention due to easy tuning of their properties by altering their synthesis parameters. Polymers and inorganics together, allow us to develop 2D nanostructures whose electrical properties can be controlled. Thus, in this project, we aim to investigate novel 2D materials followed by their structural and electrical characterizations w.r.t transistor properties. Another focus will be to fabricate vertical heterostructures by stacking different 2D materials together and investigate resulting functionalities of the stack.
CRIS-Team Scopus Importer:2023-03-20